2011
DOI: 10.1007/s12072-011-9271-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic involvement by lymphoproliferative disorders post liver transplantation: PTLD.Int. Survey

Abstract: Liver transplant patients exhibiting early deterioration of graft function or other hepatic symptoms should, in addition to assessment for rejection, be evaluated for H-PTLD. In addition, all H-PTLD patients should be evaluated for bone marrow involvement, especially if they are EBV positive. Prospective studies with large patient populations are needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
(43 reference statements)
3
13
2
Order By: Relevance
“…However, adding this to the higher rate of multi-organ PTLD in L-PTLD, this study shows a relatively more ominous disease in renal graft recipients whose liver has been complicated by PTLD compared to other disease localizations. In our previous study on liver transplant patients [9], consistent with the current study, we found that disseminated disease is significantly higher in patients representing hepatic localization for the PTLD; however, in that study, no outcome difference has been implicated. Moreover, liver recipients with hepatic PTLD were significantly older at the time of transplantation and had a shorter time to PTLD development, observations which have not been repeated in the current study on kidney recipients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, adding this to the higher rate of multi-organ PTLD in L-PTLD, this study shows a relatively more ominous disease in renal graft recipients whose liver has been complicated by PTLD compared to other disease localizations. In our previous study on liver transplant patients [9], consistent with the current study, we found that disseminated disease is significantly higher in patients representing hepatic localization for the PTLD; however, in that study, no outcome difference has been implicated. Moreover, liver recipients with hepatic PTLD were significantly older at the time of transplantation and had a shorter time to PTLD development, observations which have not been repeated in the current study on kidney recipients.…”
Section: Discussionsupporting
confidence: 91%
“…Nuckols et al [43] have also found that [43] reported a three times larger share of males in hepatic PTLD in liver recipients. In the current study, we also found that male renal recipients were significantly more likely to develop hepatic PTLD, although in our previous report on liver recipients, we did not find any gender disparity regarding liver involvement by the PTLD [9]. An interesting similar finding of the current study to our previous report on liver transplantation is heart and bone marrow involvement.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…5,6 Other factors that promote lymphoproliferation in solid organ recipients are the type of transplanted organ, the age of the recipient, viral infections other than EBV (eg, hepatotropic viruses), and the recipients' personal vulnerability to develop lymphomas. [7][8][9][10][11] Human cells express several proteins on, in, and within their cell membranes that have a high range of biological functions and can affect their resistance and weakness to several diseases, including PTLD. Several proteins have been identified in human cells, having been proposed relevant in the behavior and prognosis of PTLD.…”
Section: Introductionmentioning
confidence: 99%